The relationship between breast milk leptin and adiponectin with child body composition from 3 to 5 years: a follow‐up study. (10th November 2016) - Meyer, D. M.; Brei, C.; Stecher, L.; Much, D.; Brunner, S.; Hauner, H.
Summary: Background: Research indicates that breast milk contains bioactive components that influence metabolism in infancy and may play a role in the prevention of obesity in early childhood. In our initial study, 147 breastfeeding mother/child pairs were followed from birth to 2 years of age to examine the relationship between breast milk leptin and total adiponectin (collected at 6 weeks and 4 months postpartum) and infant body composition. Higher breast milk total adiponectin was related to greater fat mass and weight gain in children at 1 and 2 years of age, whereas leptin showed no association. Objectives/Methods: In this follow‐up, we examined the relationship between both adipokines and children's body weight, body mass index percentiles, sum of four skin‐folds, percentage of body fat, fat mass and lean body mass at 3, 4 and 5 years of age. Results: Breast milk adipokines were largely unrelated to child anthropometric measures. Conclusion: Our results do not provide significant evidence that breast milk adipokines can predict adiposity in preschool children.